THE APPLICATION OF STUDENT WORKSHEETS AS TEACHING MATERIALS LEARNING IN ISLAMIC RELIGIOUS EDUCATION TO BE MORE EFFECTIVE - Supriyadi, Agus; Mahmudi, Mahmudi; Baiturrahman, Baiturrahman; Jakfar Rohman, Muhammad Amin (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2023)
Research on student worksheets utilized at SMPN 1 regarding the usage of instructional materials The subject of PAI used descriptive qualitative research and the findings of research on the advantages of teaching materials to create and develop SMPN 1 Asembagus. teacher worksheets Teachers modify their lesson plans according to the needs of their students, the media available in the classroom, and the activities being undertaken. As a facilitator, the teacher adjusts active learning and learning to each student's pace and ability to comprehend the subject. While the use of instructional resources for student worksheets helps students master the content more quickly, students report that they like the learning experience. As a result of their increased happiness at school, students start to follow the many regulations that are set forth by both the school and society